Adenovirus type 36 regulates adipose stem cell differentiation and glucolipid metabolism through the PI3K/Akt/FoxO1/PPARγ signaling pathway - Yi Jiao; Xiaodi Liang; Jianfei Hou; Yiliyasi Aisa; Han Wu; Zhilu Zhang; Nuerbiye Nuermaimaiti; Yang Zhao; Sheng Jiang; Yaqun Guan (Lipids in Health and Disease, 2019)
Abstract Background This study aims to investigate the molecular mechanism of Adenovirus type 36 (Ad36) in adipocyte differentiation and glucolipid metabolism. Methods Rat obesity model was established by Ad36 infection and high-fat diet, respectively. Comparison of the body weight, clinical biochemical indicators, insulin sensitivity and lipid heterotopic deposition between these two models was performed. Ad36-induced adipocyte in vitro model was also established. The binding rate of FoxO1, PPARγ and its target gene promoter was detected using ChIP. The mRNA and protein expression levels of PPARγ and downstream target genes were detected by RT-PCR and Western blot, respectively. Oil red O staining was used to measure differentiation into adipocyte. Wortmannin (WM), inhibitor of PI3K, was used to act on Ad36-induced hADSCs. Results Ad36-induced obese rats did not exhibit disorders in blood glucose and blood TG, insulin resistance and lipid ectopic deposition. The expression of Adipoq, Lpin1 and Glut4 in the adipose tissue increased. Oil red O staining showed that Ad36 induced the differentiation of hAMSCs into human adipocytes in vitro. During this process, the binding rate of FoxO1 and PPARγ promoter regions was weakened. However, the binding rate of the transcription factor PPARγ to its target genes Acc, Adipoq, Lpin1 and Glut4 was enhanced, and thus increased the protein expression of P-FoxO1, PPARγ2, ACC, LPIN1, GLUT4 and ADIPOQ. The PI3K inhibitor Wortmannin reduced the expression of P-Akt, P-FoxO1 and PPARγ2, thereby inhibiting adipogenesis of hADSC. Conclusion Ad36 may promote fatty acid and triglyceride synthesis, and improve insulin sensitivity by affecting the PI3K/Akt/FoxO1/PPARγ signaling pathway.